2012
DOI: 10.1105/tpc.112.097766
|View full text |Cite
|
Sign up to set email alerts
|

AUX/LAX Genes Encode a Family of Auxin Influx Transporters That Perform Distinct Functions during Arabidopsis Development

Abstract: Auxin transport, which is mediated by specialized influx and efflux carriers, plays a major role in many aspects of plant growth and development. AUXIN1 (AUX1) has been demonstrated to encode a high-affinity auxin influx carrier. In Arabidopsis thaliana, AUX1 belongs to a small multigene family comprising four highly conserved genes (i.e., AUX1 and LIKE AUX1 [LAX] genes LAX1, LAX2, and LAX3). We report that all four members of this AUX/LAX family display auxin uptake functions. Despite the conservation of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
381
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(399 citation statements)
references
References 32 publications
11
381
0
Order By: Relevance
“…We showed that genetic and localized chemical inhibition of auxin transport significantly affected regeneration. Despite known redundancy among auxin transporters (Blilou et al, 2005;Péret et al, 2012), we detected phenotypes in single mutants, suggesting spatial compartmentalization. Supporting this idea, PIN-FORMED3 (PIN3) was expressed in the petiole vasculature whereas PIN4 was later restricted to the proliferating vascular region.…”
Section: Vasculature Proliferation and Endogenous Callus Formationmentioning
confidence: 90%
“…We showed that genetic and localized chemical inhibition of auxin transport significantly affected regeneration. Despite known redundancy among auxin transporters (Blilou et al, 2005;Péret et al, 2012), we detected phenotypes in single mutants, suggesting spatial compartmentalization. Supporting this idea, PIN-FORMED3 (PIN3) was expressed in the petiole vasculature whereas PIN4 was later restricted to the proliferating vascular region.…”
Section: Vasculature Proliferation and Endogenous Callus Formationmentioning
confidence: 90%
“…IAA is protonated in the acidic apoplast and deprotonated in the weakly basic cytosol. Uptake of the uncharged molecule occurs by AUX1/LAX (auxin1/like AUX1) uptake carriers (Péret et al, 2012) in an undirected way. Extrusion of negatively charged IAA occurs via undirected ABCB transporter-mediated efflux (Noh et al, 2001;Geisler et al, 2005) and by PIN (pin-formed) proteins that are responsible for directed auxin movement (Friml et al, 2003;Blilou et al, 2005).…”
mentioning
confidence: 99%
“…Proper plant development strictly requires the directed cell-to-cell transport of auxin, which is achieved by a system of auxin influx and efflux transporters (1). AUXIN RESISTANT1 (AUX1)/LIKE-AUX1 (LAX) proteins are auxin influx transporters and PIN-FORMED (PIN) proteins are auxin efflux transporters that may act together with ABC transporters (3)(4)(5)(6)(7)(8). Auxin transport gains its directionality through the often polar distribution of the plasma membrane-resident PIN auxin efflux carriers, PIN1-PIN4 and PIN7 in Arabidopsis thaliana (1,9).…”
mentioning
confidence: 99%